Synthesis of Pyrido[2,3-c]coumarin Derivatives by an Intramolecular Povarov Reaction - Belal, Md.; Das, Deb K.; Khan, Abu T. (Synthesis, 2015)
Fused pyrido[2,3-c]coumarin derivatives were prepared by an intramolecular Povarov reaction of 2-(propagyloxy)benzaldehydes with 3-aminocoumarins in the presence of 10 mol% of triflic acid as a catalyst in refluxing acetonitrile. Among the advantages of this protocol are shorter reaction times, good yields, and the absence of the need for aqueous workup and chromatographic separation.
Keywords: heterocycles; pyridines; coumarins; fused-ring systems; Diels–Alder reactions; cyclizations; catalysis